Digitalization and Sustainable Development: the New COVID-19 Challenge Requires Non-standard Solutions - Martynovych, Nataliia Oleksandrivna; Polishchuk, Oksana Volodymyrivna; Kulinich, Tetiana Volodymyrivna; Popova, Yuliia Mykolaivna (PAN. Komitet Człowiek i Środowisko, 2022)
The spread of Covid-19 contributes to changing economic, environmental and social reality around the world. One of the significant consequences of the current pandemic can already be called the accelerated introduction of digital technologies in various fields. Against this background, the article is devoted to the theoretical and analytical substantiation of the feasibility of reorienting traditional production and management systems in the context of Covid-19 to digital ones. It has been proven that digitalization, sustainable development and Covid-19 are new challenges generated by human activity that require non-standard solutions. A composition of non-standard digital solutions is proposed to overcome the problems associated with Covid-19, ensuring sustainable development, allowing to launch new business models capable of smoothing post-Covid consequences and bringing the world economy onto a trajectory of sustainable economic growth.

Розповсюдження Covid-19 сприяє зміні економічної, екологічної та соціальної реальності у всьому світі. Одним із значних наслідків поточної пандемії вже сьогодні можна назвати прискорене впровадження цифрових технологій у різних областях. Виходячи з цього, стаття присвячена теоретико-аналітичному обґрунтуванню доцільності переорієнтації традиційних систем виробництва та управління за умов Covid-19 на цифрові. Доведено, що цифровізація, сталий розвиток та Covid-19 – це нові виклики, породжені людською діяльністю, що потребують нестандартних рішень. Запропоновано композицію нестандартних цифрових рішень подолання проблем, пов'язаних з Covid-19, що забезпечують сталий розвиток, що дозволяють запустити нові бізнес-моделі, здатні згладити постковидні наслідки та вивести світову економіку на траєкторію сталого економічного зростання.
Keywords: sustainable development; sustainable development goals; digitalization; digital technologies; Covid-19; стійкий розвиток; цілі сталого розвитку; цифровізація; цифрові технології; Covid-19